An evaluation of the performance of XLD, DCA, MLCB, and ABC agars as direct plating media for the isolation of Salmonella enterica from faeces. Issue 4 (1st April 2002) - Nye, K J; Fallon, D; Frodsham, D; Gee, B; Graham, C; Howe, S; Messer, S; Turner, T; Warren, R E
Abstract : Aims: To compare the performance of four media, singly and in combination, as direct plating media for the isolation of Salmonella enterica from human faeces. Methods: Two thousand four hundred and nine routine, faecal samples received by four laboratories were inoculated on to xylose lysine desoxycholate (XLD), desoxycholate citrate (DCA), mannitol lysine crystal violet brilliant green (MLCB), and α-β chromogenic (ABC) agars using standardised protocols, reagents, and data collection. Isolates of presumptive salmonellae were identified using standard laboratory techniques and the results were analysed statistically. Results: Direct plating recovered 46 of the 60 possible isolates of Salmonella spp recovered via enrichment broth. No isolates were recovered from direct plating that were not recovered via selenite enrichment. MLCB gave the highest isolation rate individually (84.8%) and amounts of competing flora (CF) did not affect the recognition of colonies. ABC proved highly specific, but insensitive, and isolation rates were adversely affected by any amount of CF. Isolation rates from XLD and DCA were only affected when the CF load was heavy. DCA was least specific, with only 9.01% of picks positive and greatest number of confirmatory tests. XLD and MLCB, in combination, gave the highest isolation rate. Conclusions: Where the earlier results of direct plating may be advantageous, XLD and MLCB provide the optimal combination. For non-typhi salmonellae, MLCB is the best, single direct plating medium. For routine diagnostic work, XLD is most effective.